1999
DOI: 10.1074/jbc.274.27.19389
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Igα and Igβ Expression as a Function of B Lineage Differentiation

Abstract: Membrane-bound immunoglobulin (Ig) molecules are noncovalently bound to the transmembrane Ig␣ (CD79a) and Ig␤ (CD79b) proteins, respectively the products of the mb1 and B29 genes, to form the B cell antigen receptor (BCR) 1 complex (1). Ig␣/Ig␤ heterodimers are also integral components of pre-BCR complexes composed of surrogate light chain (LC) and heavy chains (HC) on the surface of pre-B cells (2-8). Ligation of BCR and pre-BCR initiates cytoplasmic signals via the Ig␣ and Ig␤ molecules whose cytoplasmic dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Finally, we also used Western blotting experiments with a panel of anti-CD79b mAbs directed to the extracellular domain of CD79b to confirm the existence of truncated CD79b in transfected COS-7 cells, B-cell lines, and transfected EHRB cells. These experiments revealed that protein species are generated from the alternative transcripts of CD79 and confirm the work of Benlagha et al, 34 which has recently demonstrated the truncated form of CD79a in normal B cells by Western blotting. Intriguingly, all of the anti-CD79 mAbs available bound to both full-length and truncated forms of the CD79b molecule, despite the fact that the truncated molecule has lost the complete extracellular Ig-like domain and is left with only 25 amino acids to provide the Ab epitope.…”
Section: Discussionsupporting
confidence: 76%
“…Finally, we also used Western blotting experiments with a panel of anti-CD79b mAbs directed to the extracellular domain of CD79b to confirm the existence of truncated CD79b in transfected COS-7 cells, B-cell lines, and transfected EHRB cells. These experiments revealed that protein species are generated from the alternative transcripts of CD79 and confirm the work of Benlagha et al, 34 which has recently demonstrated the truncated form of CD79a in normal B cells by Western blotting. Intriguingly, all of the anti-CD79 mAbs available bound to both full-length and truncated forms of the CD79b molecule, despite the fact that the truncated molecule has lost the complete extracellular Ig-like domain and is left with only 25 amino acids to provide the Ab epitope.…”
Section: Discussionsupporting
confidence: 76%
“…Expressed throughout B cell development (3), Lyn participates in signaling from multiple cell surface receptors. Upon engagement of surface Ig, Lyn associates with the B cell Ag receptor (BCR) 3 complex and is rapidly tyrosine phosphorylated, with an associated increase in its enzymatic activity (4 -6). Lyn is also activated after engagement of the CD40 receptor (7), and in the absence of Lyn, CD40-induced Fas expression was reported to be substantially reduced, as was germinal center (GC) formation (8,9).…”
Section: Novel Roles For Lyn In B Cellmentioning
confidence: 99%
“…While CD79b appears to be expressed as a single isoform, CD79a is expressed from two alternatively spliced transcripts, with the smaller one representing an immature form, whose protein is predicted not to form disulfide-linked dimers with CD79b but to maintain the transmembrane and cytoplasmic portions, thus permitting immunological detection. 2 Cytoplasmic (c)CD79a is expressed prior to CD19 during B lymphoid 3 development and is expressed by virtually all B-cell precursor ALLs (BCP-ALL). 4,5 It is considered to represent a B lineage restricted marker, 6 although weak cCD79a expression has been detected by immunohistochemistry or flow cytometry in 10-40% of a limited number of T-ALLs.…”
Section: Introductionmentioning
confidence: 99%